Prabowo-Gibran's Free Nutritious Food: Impacts on Human Capital and Community Economy - Tangkudung, Audrey G. (Journal of Comprehensive Science, 2025)
This research analyzes the Free Nutritious Food (MBG) Program initiated by the Prabowo-Gibran administration as a strategic policy to combat malnutrition, enhance educational outcomes, and stimulate local economic growth. Employing a qualitative approach, the research involved in-depth interviews, participatory observation, and document analysis with key stakeholders, including policymakers, educators, nutritionists, and community members. The study identifies significant public support for the program, particularly among low-income groups who experience direct benefits in children’s health and academic focus. Consistent with human capital theory, findings confirm that improved nutrition positively influences cognitive development and school participation. However, challenges such as uneven food distribution in remote areas, infrastructural constraints, and inter-agency coordination gaps threaten the program’s effectiveness. Additionally, the large-scale budget requirement (IDR 100 trillion annually) raises concerns about long-term fiscal sustainability and potential dependency. This research highlights the need for a comprehensive strategy that integrates community empowerment, nutrition education, and inter-sectoral collaboration to optimize outcomes. The study contributes to the academic discourse on social policy in Indonesia by offering an in-depth, multidimensional evaluation and suggesting practical pathways for enhancing program sustainability. The findings have significant implications for designing inclusive, efficient, and resilient public health and education interventions.